ANALYSIS OF USER SATISFACTION OF ACADEMIC DIGITAL LIBRARIES: A CASE OF UZBEKISTAN (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study was conducted to examine user satisfaction with academic digital libraries in Uzbekistan. A survey was carried out among academic users from various higher education institutions, including students and faculty members. The survey aimed to identify key factors such as information quality, system usability, service efficiency, and the availability of digital resources. The results indicated that the majority of users consider academic digital libraries beneficial for research and study purposes, with high ratings for accessibility and resource diversity. However, certain shortcomings were identified, particularly in system navigation and technical support services, which require improvements. The study highlights the necessity of continuous development in digital library infrastructure to enhance user experience. These findings provide valuable insights for policymakers and educational institutions striving to improve digital library services in Uzbekistan.